Toxicity at the cellular level of artificial synthetic flavorings (Acta Scientiarum. Biological Sciences, 2016)
The goal of the present study was to evaluate the cytotoxicity and genotoxicity of artificial synthetic flavoring agents cookie and tutti-frutti. To this end, root meristem cells of Allium cepa L. were exposed to these substances in exposure times of 24 and 48 hour using individual doses of 0.3; 0.6 and 0.9 mL and doses combined as follows: 0.3 mL + 0.3 mL; 0.6 mL and 0.9 mL + 0.6 mL + 0.9 mL. After applying the treatments, root meristems were fixed, hydrolyzed, stained and analyzed a total of 5,000 cells using an optical microscope to evaluate each dose and combined treatment. All three doses of cookie flavoring and combined treatments significantly inhibited cell division of the tissue studied. Doses of tutti-frutti caused no change in cell division rate. In addition, doses of both flavorings and treatments combining these solutions induced cell aberrations in a significant number of cells to the A. cepa system. Therefore, under these analytical conditions, cookie flavoring and combined doses were cytotoxic and genotoxic, and tutti-frutti flavoring, although non-cytotoxic, demonstrated genotoxic action.